ANALISIS PENGARUH MASA OPERASIONAL TERHADAP PENURUNAN KAPASITAS TRANSFORMATOR DISTRIBUSI DI PT PLN (PERSERO) - Sulistiyono Sulistiyono; Haris Nur Azis (Electrical Engineering, Universitas Mercu Buana, 2017)
One cause the interruption of transformer is loading that exceeds the capabilities of the transformer. The state of continuous overload will affect the age of the transformer and result in a reduced capacity of the transformer. The declining capacity, loading on the transformer will not be maximized and increase the risk of damage. Actions taken to attempt the decrease disturbances resulting from the transformer loadings are by the transformer test and known how many percent decrease in capacity of the transformer. The data from the test is used to calculate the reduction in the capacity of the transformer. Result of the research on the transformer which is not operated yet relating to the ideal state of a transformer. As for the research on the second transformer indicates how transformer which been operating for several years has decreased the capacity of the transformer. So that the second transformer can not be loaded to the maximum.